2017
DOI: 10.1536/ihj.16-578
|View full text |Cite
|
Sign up to set email alerts
|

An Infectious Pseudoaneurysm Caused by Ventricular Septal Defect Occluder in Patent Ductus Arteriosus Closure in a Two-Year-Old Child

Abstract: SummaryWe present a case of an infectious pseudoaneurysm after patent ductus arteriosus (PDA) closure with a ventricular septal defect (VSD) occluder in a two-year-old child. The aneurysm grew rapidly but was successfully removed in time and the patient survived. To our knowledge, this is the first report of an infectious pseudoaneurysm caused by VSD occluder in PDA closure.(Int Heart J 2017; 58: 1017-1019) Key words: Aneurysmal dilatation, Infectious endocarditis, Transcatheter A neurysmal dilatation of ductu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…[23] отметили полное прерывание резидуального кро-вотока только у 45,3% в 1-е сутки, у 71% через сутки, у 95% через месяц и у 100% к концу 1-го года после операции. Сохранение кровотока через тромбирующийся окклюдер ведет к высокому риску инфекционных и тромбоэмболических осложнений, гемолиза, а также предпосылок для формирования аневризмы протока [24,25].…”
Section: Discussionunclassified
“…[23] отметили полное прерывание резидуального кро-вотока только у 45,3% в 1-е сутки, у 71% через сутки, у 95% через месяц и у 100% к концу 1-го года после операции. Сохранение кровотока через тромбирующийся окклюдер ведет к высокому риску инфекционных и тромбоэмболических осложнений, гемолиза, а также предпосылок для формирования аневризмы протока [24,25].…”
Section: Discussionunclassified
“…1) Recently, successful transcatheter PDA closure using a commercially available device has been reported. 1,[3][4][5]13,14) Zahn et al 1) first reported transcatheter PDA closure using AVP II in extremely premature neonates. In their study, 6 preterm infants underwent transcatheter PDA closure using AVP II.…”
Section: Discussionmentioning
confidence: 99%
“…There are two approaches for mechanical ductal closure: surgery or percutaneous catheter closure. Although not without rare complications, 1) percutaneous catheter closure is now widely used, 2) considering its lower-level invasiveness and effectiveness comparable to that of surgery.…”
mentioning
confidence: 99%